FORMULASI BODY SCRUB EKSTRAK DAUN LABU AIR (LAGENARIA SICERARIA (MOLINA) STANDL.) SEBAGAI ANTIOKSIDAN: Formulation of Body Scrub Containing Bottle Gourd Leaf Extract (Lagenaria siceraria (Molina) Standl.) as an Antioxidant - Auliana Auliana; Yulistia Budianti Soemarie; Nily Su'aida (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2026)
Abstract Free radicals can cause skin cell damage and accelerate premature aging; therefore, natural antioxidants are needed and can be developed into topical cosmetic preparations. Bottle gourd leaves (Lagenaria siceraria (Molina) Standl.) are known to contain secondary metabolites with potential antioxidant activity. This study aimed to formulate bottle gourd leaf extract into a body scrub, evaluate its physical quality, and determine its antioxidant activity using the ABTS method in vitro. This experimental study included plant identification, phytochemical screening, and the formulation of a body scrub with extract concentrations of 3%, 5%, and 7%. The results showed an extract yield of 17.31% and the presence of alkaloids, phenolics, flavonoids, tannins, saponins, and triterpenoids. Physical evaluation indicated that all formulations met the requirements of semisolid preparations, with pH values of 6.97–7.37, viscosity of 2646–9596 cPs, spreadability of approximately 5 cm, and good stability. Antioxidant activity testing showed that the positive control, ascorbic acid, had an IC₅₀ value of 2.95 ppm, while the extract and body scrub did not exhibit IC₅₀ values at the tested concentrations. This may be due to low levels of active compounds or interactions with the formulation matrix; therefore, further studies using higher concentrations or different methods are recommended. Keywords: Bottle Gourd Leaf, Body scrub, Secondary Metabolites, Free Radicals ABTS (2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)).